Acute chorioamnionitis in pregnancies complicated by placental abruption and short-term neonatal outcomes: A retrospective cohort study. (December 2022) - Oltean, Irina; Tran, Jason; Mavedatnia, Dorsa; Lawrence, Sarah; Tristani, Lauren; Moretti, Felipe; El Demellawy, Dina
Abstract: We examined neonatal outcomes in pregnancies complicated by placental abruption (PA) and acute chorioamnionitis (CA). Exposure was acute CA; primary outcome - fetal death; secondary outcomes - adverse Apgar score, neonatal intensive care unit (NICU) admission, and cardiac depression. 267 placentas - 18.4% exhibited acute CA. PA pregnancies with CA - 29% experienced fetal death. Funisitis, acute CA and adverse neonatal outcomes are dependent. Without accounting for funisitis, aforementioned findings hold, though effect sizes are smaller. PA, acute CA with funisitis could affect fetal death and NICU admission. Acute CA and PA alone could impact fetal death and adverse Apgar scores. Highlights: We examined if pregnancies complicated by PA and acute CA worsen neonatal outcomes. Acute CA with funisitis may affect fetal death and NICU admission in PA pregnancies. Acute CA impacts fetal death and adverse Apgar scores.